The Effect of two Weeks of Severe Periodic Training on SDF-1α Protein, its Receptor (CXCR4) and C-Kit in the Heart of Male Rats - H Rajabi; F Nasirinezhad; M Bapiran; F Ramezani (Armaghane Danesh Bimonthly Journal, 2018)
Abstract